1997
DOI: 10.1111/j.1440-172x.1997.tb00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation: The death/life paradox

Abstract: Transplantation of organs has increased dramatically over the last 3 decades. The Australian National Liver Transplant Unit was established in 1985 at Royal Prince Alfred Hospital. Their first 5 years was reported in a paper in 1992 in which survival was defined as 'going home'. The study reported in this paper followed a 3 year study with one woman who experienced a liver transplant in which survival had many dimensions, of which going home was not one. This post doctoral study of 2 years extended the earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Using the method of grounded theory, Wainwright describes the process of transformation, moving through a five‐stage trajectory of receiving the transplant, improving in hospital, improving at home, feeling well again, and reciprocating. In a qualitative study of eight liver‐transplanted patients, the paradox of facing life and death at the same time was highlighted by Lumby in 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Using the method of grounded theory, Wainwright describes the process of transformation, moving through a five‐stage trajectory of receiving the transplant, improving in hospital, improving at home, feeling well again, and reciprocating. In a qualitative study of eight liver‐transplanted patients, the paradox of facing life and death at the same time was highlighted by Lumby in 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety is a symptom commonly experienced in post-Tx [51,52]. One year after LTx, studies have shown a negative effect of anxiety on long-term health and quality of life impairment [53,54].…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
“…The first author of this article, herself a liver transplantation recipient, found that clinically based QOL instruments, such as the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36) (Hill, Harries, & Popay, 1993;Wainwright, 2011a), did not sufficiently address the characteristics of post-operative wellbeing that were significant to her. Other researchers (Blanch et al, 2004;Littlefield et al, 1996;Lumby, 1997) have noted that generic measures do not necessarily capture important transplantspecific domains based on the lived experience of liver transplantation recipients.…”
Section: Original Articlementioning
confidence: 99%
“…The development in this field is reflected in its associated body of literature in that it has been dominated by clinically focused research articles (Forsberg, Bäckman, & Möller, 2000;Robertson, 1999). In the early days of liver transplantation, recovery meant simply going home (Lumby, 1997) and little was known about the quality of life (QOL) for recipients as they moved beyond recovery, returned to their families and communities and resumed their lives. There are various definitions of QOL depending on the associated paradigm (Walker & Lowenstein, 2009)…”
mentioning
confidence: 99%